2013
DOI: 10.1088/0004-637x/773/2/166
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Moreton Wave and Wave-Filament Interactions Associated With the Renowned X9 Flare on 1990 May 24

Abstract: Using Big Bear Solar Observatory film data recently digitized at NJIT, we investigate a Moreton wave associated with an X9 flare on 1990 May 24, as well as its interactions with four filaments F1-F4 located close to the flaring region. The interaction yields interesting insight into physical properties of both the wave and the filaments. The first clear Moreton wavefront appears at the flaring-region periphery at approximately the same time as the peak of a microwave burst and the first of two γ -ray peaks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 64 publications
(84 reference statements)
3
37
0
2
Order By: Relevance
“…A comprehensive analysis of the secondaries is available for the historic GLE 48 of 1990 May 24 (see in particular Kocharov et al 1994Kocharov et al , 1996aKocharov et al , 1996b. There were no direct observations of associated CME, but a global wave on the solar surface was observed, with a Moreton wave of speed 1500-2600kms −1 (Liu et al 2013). Referring to other events, CME speed may be 1.3-2 times the speed of a Moreton wave on the Sun (e.g., Pohjolainen et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive analysis of the secondaries is available for the historic GLE 48 of 1990 May 24 (see in particular Kocharov et al 1994Kocharov et al , 1996aKocharov et al , 1996b. There were no direct observations of associated CME, but a global wave on the solar surface was observed, with a Moreton wave of speed 1500-2600kms −1 (Liu et al 2013). Referring to other events, CME speed may be 1.3-2 times the speed of a Moreton wave on the Sun (e.g., Pohjolainen et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Inferring the elusive coronal magnetic field is one of the primary goals of coronal seismology, which complements other approaches including polarimetric measurements using Zeeman and Hanle effects (Lin, Penn, and Tomczyk, 2000), extrapolations of surface magnetograms (Zhao and Hoeksema, 1994;De Rosa et al, 2009), and radio observations of gyro-resonance emission (Gary and Hurford, 1994;White and Kundu, 1997). The fast-magnetosonic speed weakly depends on the direction of the wave vector with respect to the magnetic field, which has a strong vertical component in the quiet Sun and is thus practically assumed to be perpendicular to the predominantly horizontal EIT wave vectors.…”
Section: Magneto-seismologymentioning
confidence: 99%
“…It has been known for a long time that Moreton waves can cause filament oscillations (Moreton, 1960(Moreton, , 1964Ramsey and Smith, 1966;Liu et al, 2013), which are usually observed as "winking filaments". If the line-of sight component of the oscillation exceeds 20 km s -1 , the filament vanishes from and subsequently reappears in Hα line center filtergrams (for a review of filament oscillations, see Arregui et al, 2012).…”
Section: Excitation Of Oscillationsmentioning
confidence: 99%